Atypical working hours are associated with tobacco, cannabis and alcohol use: Nadine Hamieh. (25th October 2022) - Hamieh, N; Airagnes, G; Descatha, A; Goldberg, M; Limosin, F; Roquelaure, Y; Lemogne, C; Zins, M; Matta, J
Abstract: Background: We examined prospective associations between atypical working hours, substance use and sugar and fat consumption. Methods: In the French population-based CONSTANCES cohort, 47, 288 men and 53, 324 women currently employed included between 2012 and 2017 were annually followed for tobacco and cannabis use; among them, 35, 647 men and 39, 767 women included between 2012 and 2016 were also followed for alcohol and sugar and fat consumption. Three indicators of atypical working hours were self-reported at baseline: working at night, weekend work and non-fixed working hours. Generalized linear models computed odds of substance use and sugar and fat consumption at follow-up according to atypical working hours at baseline while adjusting for sociodemographic factors, depression and baseline substance use if appropriate. Results: Working at night was associated with increased tobacco use in women [odds ratios ranging from 1.45 to 1.48], with increased cannabis use in men [from 1.40 to 1.54] and with increased alcohol use in both men and women [from 1.12 to 1.14]. Weekend work and non-fixed working hours were associated with increased tobacco and alcohol use in both men and women [from 1.15 to 1.54 and 1.12 to 1.14, respectively]. Dose-dependent relationships were found regarding the association between working at night and tobacco use in women as well as regarding non-fixed working hours and tobacco use in both men and women (P for trends <0.001). Conclusions: The potential role of atypical working hours on substance use should be considered by public health policy makers and clinicians in information and prevention strategies. Key messages:  Night shifts were associated with increased smoking in women with dose-dependent relationships, cannabis use in men and alcohol use in both.  Weekend work and non-fixed working hours were associated with increased alcohol and tobacco use with dose-dependent relationships in men and women.